Effectiveness of Group Counseling Cognitive Restructuring Technique Model to Reduce Students' Interpersonal Communication Anxiety - Saputra, Anugrah Ragil; Japar, Muhammad; Putro, Hijrah Eko (Prosiding University Research Colloquium, 2022)
This study aims to determine the effect of group counseling on cognitive restructuring techniques to reduce student interpersonal communication anxiety. This type of research is a quantitative research with a pre-experimental design research method with a one group pretest-posttest design model. The sample in this study was 15 students of FKIP Muhammadiyah University of Magelang who were taken using purposive sampling technique. The data collection tool used is a student interpersonal communication anxiety scale. Based on the results of hypothesis testing with the paired sample t-test with a significant (2-tiled) probability of 0.000 <0.05. And based on the results of the analysis and discussion, there is a difference in the average score of the student interpersonal communication anxiety scale questionnaire by 25% from the pretest results and the posttest results of the student interpersonal communication anxiety scale questionnaire.